Considerações acerca da tributação dos contratos de licenciamento e cessão de direito de uso de software à luz da Constituição Federal de 1988 - Kfouri, Maira Canan (2021)
Due to the paradigm shift driven by the digital economy at the end of the 20th century new business models and operational dynamics arise. Accordingly, use and consumption of software features and functionalities have increased at a global level. Simultaneously, existing rules does not seem to be appropriate neither efficient to deal with uncertainties and new situations derived from increased digitalization, mainly because of the original (tangibility) assumption behind such rules. The main goal of the study is to assess Brazilian tax impacts triggered by use and consumption of software attribute and applications, more specifically, to assess potential tax impacts derived from software license and right to use software. With that in mind, the study should consider fundamental aspects of the digital economy; increased relevance of intangible assets to the new economy; current legal treatment provided by Brazilian law to intangible assets; and Constitutional rule on taxation and on the Brazilian consumption taxes (i.e., the State VAT, Service Tax and Excise Tax)